Noncentrosymmetric superconductivity and peak effect in rhenium based materials - Abud, Fábio Santos Alves (2021)
The present manuscript provides a detailed and systematic experimental study of the superconducting properties of noncentrosymmetric (NCS) Re3M (M = W, Ta, and Nb) materials with high rhenium atomic concentration. Owing to the lack of a center of inversion within the α-Mn NCS crystal structure, which develops in the Re-M binary systems, novel properties of the superconducting ground state may arise if the otherwise prohibited spin singlet-triplet admixture is realized. In addition to likely posses strong anti-symmetric spin-orbit coupling, the Re3M compounds are weakly correlated materials. Some aspects of this study include the stabilization of the α-Mn phase via the partial atomic substitution of W by Nb or Ta and/or the annealing procedures at T = 1700 °C in Re3M materials. Physical characterization through temperature and magnetic field dependent resistivity ρ(T,H), specific heat Cp(T,H), thermal conductivity κ(T,H), and magnetization M(T,H) of both single and multi phase Re3M specimens, and the indirect study of flux pinning dynamics emerging close to the upper critical field (Hc2) were conducted. Polycrystalline samples of Re3MxW1-x solid solutions, M = Ta and Nb, and 0.0 ≤ x ≤ 0.5, and Re1-yWy compounds, 0.1 ≤ y ≤ 0.5, were synthesized in an arc melting furnace and subsequently annealed at high temperatures under vacuum or inert atmosphere. From X-ray diffraction results, it is found that the α-Mn structure is stabilized in the Re3Ta and Re3Nb as cast materials, while the Re3W material needs the heat treatment at T = 1700 °C to acquire a single α-Mn phase structure. In as cast samples, the partial atomic substitution in the Re3MxW1-x solid solutions is effective to stabilize the NCS structure when the tungsten content is below 75 at.\\% (x > 0.25). Two superconducting phases are believed to emerge in the centrosymmetric, as cast Re3W material due to the two clear peaks in its specific heat results. In contrast, the annealed Re1-yWy NCS materials, 0.25 ≤ y ≤ 0.28, exhibit a single, well-defined peak marking the superconducting transition in specific heat results. However, the HxT phase diagram of the annealed Re3W sample contains a bifurcation in the lowest temperature limit: two superconducting boundary lines mark a region with magnetic field quasi-independent electrical resistance curves. The Re3Ta HxT phase diagram also displays an unconventional feature, even though all other physical properties probed here suggest a conventional, isotropic s-wave pairing. In the annealed solid solutions Re3M0.5W0.5, the ρ(T,H) features related to the peak effect (PE), where a maximum in the superconducting critical current Jc occurs in the vicinity of Hc2(T) boundary line, are more pronounced. Moreover, in the PE region, re-entrant and irreversible behaviors arise in the magneto-transport curves. Conversely, the PE is almost imperceptible in the results of the magnetic properties of Re3M materials. To summarize, our main findings are that the low temperature thermodynamic data strongly suggest conventional, nodeless superconductivity in Re3M NCS materials and the magneto-transport data near the phase boundary Hc2(T) exhibit features associated with the PE in all single α-Mn phase materials, being more pronounced in the annealed solid solution specimens.